Iraqi Rural Singing and National Identity: مصطفى عباس السوداني-عبد الحليم أحمد حسن (Al-Academy, 2020)
Singing has significant importance being a major basis for the expressive and cultural production of the societies and a real companion that reflects their artistic career and is strongly connected to the reality of the peoples and the production of the individuals, who are geniuses of arts and culture. Rural singing represents one of the most well-known artistic singing styles in Iraq, which truly embodied the Iraqi national identity. However, it remained confined to the countryside and did not spread due to the lack of mass media and the recording technologies at that time. It has been pure virgin singing art. The theoretical framework is divided into three axes:• The Iraqi singing heritage in the twentieth century, a historical perspective: the two researchers reviewed the types of singing arts in Iraq, and their variation due to their different culture and phonemic norms and the geography of the areas that they inhabit, and the heritage of the Iraqi singing in the period specified within the research limits, passing through the rural singing in the southern provinces and the immigration of some male and female singers from the countryside to the city of Baghdad and offering their rural productions and singing the (Abu- theyyah) in the coffee shops of Baghdad. The research, then, reviews the record revolution and the record companies which documented many of the Iraqi songs of different artistic styles such as (peste, abu theyyah,) the rural genres, in addition to the methods of writing the folk literature, especially the dramatic one. The research concludes with a review of the rural singing career until the end of the seventies.• The second section entitled the national identity: in which the two researchers review four paragraphs through which the patterns and styles of singing and musical artistic productions can be identified. They also studied what makes them national identity of any nationality or specific country and identified the singing and music identity in general, and the Iraqi in specific.• The third section in which the researchers review the famous singers of the Iraqi rural singing. The rural song in the seventies of the twentieth century represents a new production of the rural singing with poetic texts from the literature of the south and the middle, and the melodies of these songs blended the purity of the countryside with the characteristic of sadness which is clear in its melodies and the spirit of prevailing Egyptian melodies of the East.• The research concluded with recommendations and suggestions to preserve the singing and musical heritage in general.